Adolescent Mental Health in the Context of Social Media – Focus on Social Anxiety and Depression - Hanum Retno Hanifah; Adnanto Wiweko; I Made Danuarta Wiguna; Shira Putri Wardana; I Nyoman Dio Yudha Prawira (Indonesian Publication Center, 2026)
This literature review explores the complex relationship between social media use and adolescent mental health, with a particular focus on social anxiety and depression. In the digital era, social media plays a major role in shaping adolescents’ self-identity and emotional well-being. This review synthesizes findings from various recent studies and analyzes how excessive and uncontrolled use of social media can damage self-perception, encourage unhealthy social comparisons, and trigger psychological disorders. Using a systematic literature review method, the study identifies key internal and external factors in identity formation—such as family, peers, and role models—and how these interact with social media. It also explores the emotional impact of phenomena such as Fear of Missing Out (FoMO), the influence of social feedback on the brain’s reward system, and stress responses involving the hypothalamic-pituitary-adrenal (HPA) axis. Finally, the review identifies relevant intervention methods, such as internet-based cognitive behavioral therapy (iCBT), as approaches to address the negative effects of social media. The findings highlight the dual role of social media as both a platform for self-expression and a source of emotional stress. The recommendations emphasize the importance of digital literacy, parental involvement, and public policy in promoting healthy social media habits. The study concludes that a multidisciplinary approach is essential to support adolescent mental health in an ever-evolving digital world.